Novel 4-aminoquinazoline derivatives as new leads for anticancer drug discovery - Ghorab Mostafa M.; Alsaid Mansour S. (Acta Pharmaceutica)
A novel series of quinazoline derivatives 2-8, 10-12 were designed and synthesized. Structures of the newly synthesized compounds were confirmed by elemental analyses, IR, 1H and 13C NMR spectral data. All the newly synthesized compounds were evaluated for in vitro cytotoxic activity against the breast cancer cell line MCF-7. Seven of the novel compounds exhibited higher activity than the reference drug doxorubicin. The corresponding compounds 3, 4, 5, 8, 10, 11 and 12 exhibited higher activity with IC50 values from 22.75 to 43.44 μmol L−1, compared to the reference drug doxorubicin with IC50 value of 47.90 μmol L−1. Also, compounds 1, 6, and 9 are nearly as active as doxorubicin with IC50 values of 48.31, 48.90, and 48.91 μmol L−1, respectively, while compounds 2 and 7 exhibited a moderate activity with IC50 values of 50.44 and 52.37 μmol L−1. In addition, compound 13 showed no activity. Cytotoxic screening of the tested copmpounds offered an encouraging framework that may lead to the discovery of potent anti-breast cancer activity.